Levosimendan: beyond its simple inotropic effect in heart failure. - Antoniades, C; Tousoulis, D; Koumallos, N; Marinou, K; Stefanadis, C (2007)
Classic inotropic agents provide short-term haemodynamic improvement in patients with heart failure, but their use has been associated with poor prognosis. A new category of inotropic agents, the Ca(2+) sensitizers, may provide an alternative longer lasting solution. Levosimendan is a relatively new Ca(2+) sensitizer which offers haemodynamic and symptomatic improvement by combining a positive inotropic action via Ca(2+) sensitization and a vasodilatory effect via adenosine triphosphate(ATP)-sensitive K(+) (K(ATP)), Ca(2+)-activated K(+) (K(Ca)(2+)) and voltage-dependent K(+) (K(V)) channels activation. Levosimendan also seems to induce a prolonged haemodynamic improvement in patients with heart failure as a result of the long half-life of its active metabolite, OR-1896. Furthermore, there is also evidence that levosimendan may have additional antiinflammatory and antiapoptotic properties, affecting important pathways in the pathophysiology of heart failure. Despite the initial reports for a clear benefit of levosimendan on short- and long-term mortality in patients with severe heart failure, the results from the recent clinical trials are rather disappointing, and it is still unclear whether it is superior to dobutamine in affecting survival of patients with severe heart failure. In conclusion, levosimendan is a promising agent for the treatment of decompensated heart failure. As further to its positive inotropic effect, it affects multiple pathways with key roles in the pathophysiology of heart failure. The results of the ongoing trials examining the effect of levosimendan on mortality in patients with heart failure will hopefully resolve the controversy as to whether levosimendan is superior to classic inotropic agents for the treatment of severe heart failure.